1980
DOI: 10.1148/radiology.136.3.6773105
|View full text |Cite
|
Sign up to set email alerts
|

External irradiation for malignant thyroid tumors.

Abstract: Thirty-eight patients with residual or recurrent primary thyroid cancers which did not take up 1-131 were treated with external beam irradiation. Excluding 5 patients with malignant lymphoma, there were 23 patients with local disease and 10 with distant metastases. Doses ranged from 3,500 to 7,000 rads (35-70 Gy) among the 23 with local disease; local tumor control was achieved in 8. Six are alive and well 2-11 years later. External beam irradiation should be considered in locally advanced, incompletely resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…During this limited follow-up study, the 5-and 10-year survival rates were comparable with those in previous studies [24]. The role of adjuvant external radiotherapy for the post-operative treatment of well differentiated human thyroid cancer is still a controversial issue [25,26], although its use has been reported in patients with well-differentiated thyroid cancer with post-operative residual disease, local recurrence, or in 1311 treatment refractory patients [27,28]. In a recent study with a limited followup, Lin et al [29] found that external radiotherapy did not improve the survival of patients with welldifferentiated thyroid cancer at an advanced clinical stage.…”
supporting
confidence: 76%
“…During this limited follow-up study, the 5-and 10-year survival rates were comparable with those in previous studies [24]. The role of adjuvant external radiotherapy for the post-operative treatment of well differentiated human thyroid cancer is still a controversial issue [25,26], although its use has been reported in patients with well-differentiated thyroid cancer with post-operative residual disease, local recurrence, or in 1311 treatment refractory patients [27,28]. In a recent study with a limited followup, Lin et al [29] found that external radiotherapy did not improve the survival of patients with welldifferentiated thyroid cancer at an advanced clinical stage.…”
supporting
confidence: 76%
“…3 Occasional reports have described good results in undifferentiated thyroid carcinoma with radiation therapy alone or in combination with chemotherapy. 6,7 However, in these reports the small-cell type anaplastic lesions, which usually respond well to radiation and chemotherapy and carry a much better prognosis, were not classified and analyzed separately, therefore creating a misleading favorable bias. Furthermore, on routine light microscopic examination, many pathologists find the spindle and giant cell variants indistinguishable from large cell lymphomas, which are also more responsive to radiation and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…All reported series are retrospective by nature. Recent data indicate that external radiotherapy can be used for curative treatment in patients with microscopic residual or gross disease after surgery [17,18]. Tubiana et al [8] reported similar survival rates for patients who received postoperative irradiation and for those who received surgery alone.…”
Section: Medullary Thyroid Cancermentioning
confidence: 99%